Evaluation of BaP in breathing zone of asphalt workers in Tehran - H Kakoei; H Aghaei; J SHahtaheri; F Omidi; S Arefian; K Azam; Sh Resalati (طب کار)
Background: Asphalt workers are exposed to dangerous agents in his workplace that might result in occupational diseases. Benzo (a) pyrene as a human carcinogen, is emission from hot asphalt and asphalt workers are exposed with it. The aim of this study was, evaluation of respiratory exposure to benzo (a) pyrene among asphalt workers. Method: In this study, 42 samples were collected from breathing zone of asphalt workers under supervision of Tehran Municipality. The samples were taken by sorbent tube and filter connected to a personal sampling pump. Analysis of samples were done by HPLC – UV. Result: The results indicated that, of 42 samples, 71 percent equivalent to 30 samples, benzo (a) pyrene were detected. Screedman among all jobs has the highest concentration with a mean and standard deviation of 38.83 and 17.74 respectively. No benzo (a) pyrene was detected in oil man task in any of the samples. Scheffe test showed that screedman and roller driver have significant differences (0.03). Conclusion: Result have shown that the concentration of benzo (a) pyrene was the most and least at screed man and roller driver jobs respectively. In addition occupational exposure to benzo (a) pyrene is lower than Threshold Limit Value by related organizations.